ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. HYMSA INDOTRACO CIREBON - Wicaksono, Triadhy; Rahardjo, Mudji (Diponegoro Journal of Management, 2015)
This research is motivated by the research gap from previous studies where there is difference result between on study with other studies. This study aimes to analyze the effect of transformational leadership style and compensation to employees satisfaction PT. Hymsa Indotraco Cirebon.The population used in this study were all employees of PT. Hymsa Indotraco numbering 125 people. Based on the calculation formula Slovin, the samples were determined by 95 people. The sampling technique was conducted by the method of proportionate stratified random sampling. The analytical method used is multiple regression analysis. The results of a study reported regression equation as follows: Job Satisfaction = 0,382X1 + 0,376X2.Based on the test instrument, the indicators are valid and reliable. In the classical assumption, there are no symptoms multicoloniarity, does not occur heterocedastity, and normal distribution of data. The coefficient of determination shows the figure of 0,478 which means that the variables of job satisfaction is influenced by variables of transformational leadership style and compensation amounting to 47,3 %. The results showed that transformational leadership style and compensation positive and significant impact on job satisfaction of employees of PT . Hymsa Indotraco Cirebon either partially or simultaneously.